Enolase: A Key Player in the Metabolism and a Probable Virulence Factor of Trypanosomatid Parasites—Perspectives for Its Use as a Therapeutic Target. (22nd March 2011) - Avilán, Luisana; Gualdrón-López, Melisa; Quiñones, Wilfredo; González-González, Limari; Hannaert, Véronique; Michels, Paul A. M.; Concepción, Juan-Luis
Abstract : Glycolysis and glyconeogenesis play crucial roles in the ATP supply and synthesis of glycoconjugates, important for the viability and virulence, respectively, of the human-pathogenic stages of Trypanosoma brucei, Trypanosoma cruzi, and Leishmania spp. These pathways are, therefore, candidate targets for antiparasite drugs. The glycolytic/gluconeogenic enzyme enolase is generally highly conserved, with similar overall fold and identical catalytic residues in all organisms. Nonetheless, potentially important differences exist between the trypanosomatid and host enzymes, with three unique, reactive residues close to the active site of the former that might be exploited for the development of new drugs. In addition, enolase is found both in the secretome and in association with the surface of Leishmania spp. where it probably functions as plasminogen receptor, playing a role in the parasite's invasiveness and virulence, a function possibly also present in the other trypanosomatids. This location and possible function of enolase offer additional perspectives for both drug discovery and vaccination.